Site index and height growth curves for Pinus oocarpa Schiede in Central Honduras - Stiff, C.T; Perez, D.N; Johnson, F.D (IICA, San José (Costa Rica), 2021)
7 páginas : Incluye 4 figuras y dos tablas.